Nunn's chess openings - Nunn, John...[et al]; Burgess, Graham; Emms, John; Gallaher, Joe (London Everyman, 2014)
In this book four expert authors share their knowledge of all chess openings, offering original analysis and reference tables that have been computer-checked for accuracy.
Keywords: Chess